THE USE OF PRESUPPOSITION IN THE REVENANT MOVIE - Amstrong, Neil; Merianti, Merianti; Rahmawati, Rahmawati (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
This study focuses on the use of existential, factive, non-factive, lexical, structural, and counterfactual presupposition in Revenant movie script. The objective of this study is to describe the use of presupposition in The Revenant movie script. This study applies a qualitative descriptive design where the primary data are taken from Revenant movie script by Mark L. Smith. The data are collected by searching, reading, watching, making notes, selecting and coding the data. Then, the data are analyzed by presenting, describing, interpreting, and concluding the data. The results show that the use of Presupposition in The Revenant movie script can be classified into existential, factive, lexical, structural and counterfactual presuppositions. Only non-factive presupposition is not found in the script of the movie. From the finding it can be concluded that contextual meaning plays an important role in interpreting the meaning of presupposition. The data in the finding also shows that lexical presupposition is the most dominant presupposition type.